The Continuing Challenge of Metallo-β-Lactamase Inhibition: Mechanism Matters. (July 2018) - Ju, Lin-Cheng; Cheng, Zishuo; Fast, Walter; Bonomo, Robert A.; Crowder, Michael W.
Abstract : Metallo-β-lactamases (MBLs) are a significant clinical problem because they hydrolyze and inactivate nearly all β-lactam-containing antibiotics. These 'lifesaving drugs' constitute >50% of the available contemporary antibiotic arsenal. Despite the global spread of MBLs, MBL inhibitors have not yet appeared in clinical trials. Most MBL inhibitors target active site zinc ions and vary in mechanism from ternary complex formation to metal ion stripping. Importantly, differences in mechanism can impact pharmacology in terms of reversibility, target selectivity, and structure–activity relationship interpretation. This review surveys the mechanisms of MBL inhibitors and describes methods that determine the mechanism of inhibition to guide development of future therapeutics. Highlights: Clinical resistance to β-lactam-containing antibiotics due to bacterial expression of metallo-β-lactamases (MBLs) is becoming more prevalent and problematic. MBL inhibitors have been reported, but the mechanism of inhibition is unknown for many of these inhibitors. Mechanism of inhibition impacts the reversibility, selectivity, and interpretation of structure–activity relationships and should be strongly considered in inhibitor development. Biochemical and structural studies can be used to demonstrate the mechanism of inhibition and this information can be used to guide lead optimization.